Preharvest Treatment with Oxalic Acid Improves Postharvest Storage of Lemon Fruit by Stimulation of the Antioxidant System and Phenolic Content - Vicente Serna-Escolano; María José Giménez; Salvador Castillo; Juan Miguel Valverde; Domingo Martínez-Romero; Fabián Guillén; María Serrano; Daniel Valero; Pedro Javier Zapata (MDPI AG, 2021)
Lemon trees (Citrus limon (L.) Burm. F) were treated monthly with oxalic acid (OA) at 0.1, 0.5, and 1 mM from initial fruit growth on the tree until harvest in2019. The experiment was repeated in 2020, with the application of OA 1 mM (according to the best results of 2019). In both years, fruit from OA-treated trees and the controls were stored for 35 days at 10 °C. Results showed that all treatments reduced weight loss (WL) and maintained higher firmness, total soluble solids (TSS), and total acidity (TA) than in the controls. Meanwhile, colour (hue angle) did not show significant differences. The activity of antioxidant enzymes, catalase (CAT), ascorbate peroxidase (APX), and peroxidase (POD) in the flavedo of the fruit from the OA-treated trees was higher than in the controls at harvest and after 35 days of storage. Similarly, the total phenolic content (TPC) in the flavedo and juice of the fruit from the OA-treated trees were higher than in the controls. The increase in the activity of the antioxidant enzymes and TPC started with the first preharvest OA treatment and were maintained during fruit development on the tree until harvest. Preharvest OA treatments enhanced the antioxidant system of the lemon fruits, reducing the postharvest incidence of decay. Thus, OA could be a useful tool to increase the quality and functional properties of lemon fruits.